2019
DOI: 10.1021/acsomega.9b01862
|View full text |Cite
|
Sign up to set email alerts
|

C–S Bonds in Sulfur-Embedded Graphene, Carbon Nanotubes, and Flake Graphite Cathodes for Lithium–Sulfur Batteries

Abstract: Lithium–sulfur (Li–S) batteries are excellent rechargeable battery candidates which are extraordinarily promising as they exhibit superior specific capacity and well-known energy density; they are cost-effective and environmentally benign. Nevertheless, a few technical issues pose a significant challenge on the path to industrial applications, namely, capacity fade and Coulombic efficiency decay, which are inherent in the soluble polysulfide shuttle effect during charge/discharge cycling. Carbon materials whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…To further study the surface area and the porous structure of the carbonized materials, N 2 adsorption–desorption analysis was performed. The N 2 adsorption–desorption isotherm of the GL-I-800 shows a type III isotherm indicating the nonhomogeneous mesoporous systems ( Figure 1 h) [ 29 ]. The BET (Brunauer–Emmett–Teller) surface area and the pore volume of GL-I-800 are 844 m 2 g −1 and 1.6 cm 3 g −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further study the surface area and the porous structure of the carbonized materials, N 2 adsorption–desorption analysis was performed. The N 2 adsorption–desorption isotherm of the GL-I-800 shows a type III isotherm indicating the nonhomogeneous mesoporous systems ( Figure 1 h) [ 29 ]. The BET (Brunauer–Emmett–Teller) surface area and the pore volume of GL-I-800 are 844 m 2 g −1 and 1.6 cm 3 g −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Interconnected porous CNT promotes lithium-ion diffusion and electrical conductivity [ 28 ]. A study compared and examined polysulfide’s confinement ability by introducing sulfur into distinct types of carbon structures such as graphene, flake graphite, and CNTs [ 29 ]. Graphene/S showed the best cycle stability and reversibility at a low current density.…”
Section: Introductionmentioning
confidence: 99%
“…The composition, thermal stability and possible intermediate products could be obtained by analyzing the thermogravimetric curve [44]. Feng et al [46] studied three graphene materials with different structures as the cathode of lithium-sulfur batteries. Pure sulfur has the characteristic of one-step weight loss in the temperature range of 190-300 • C by TGA.…”
Section: Characterization Of Graphene-based Nanocompositesmentioning
confidence: 99%
“…Some of these nanoparticles can promote amyloid formations by acting as a critical nucleus, while other nanoparticles can prevent the formation of amyloid fibrils by disrupting the amyloid’s secondary structure or acting as chaperones. , Chaperones are particles that help proteins retain their natural formation, prevent protein aggregation, and form a central nucleus . It was observed that nanoparticles such as graphene quantum dots, iron oxide nanoparticles, gold nanoparticles, and amine-functionalized mesoporous silica nanoparticles can inhibit the amyloid formation and can be utilized for developing a cure for PD. In addition, it has been shown that graphene can destabilize α-synuclein amyloids and prevent aggregation. , …”
Section: Introductionmentioning
confidence: 99%
“…12−17 In addition, it has been shown that graphene can destabilize α-synuclein amyloids and prevent aggregation. 18,19 Given the importance of preventing the folding and aggregation of α-synuclein that cause amyloid formation prevention, it is imperative to work more on novel structures for PD treatment. Doped carbon nanomaterials are highly tunable and can be optimized to enhance their interaction capabilities using several dopants.…”
Section: Introductionmentioning
confidence: 99%